Picosecond Raman Excitation Profile and Transient Absorption Spectrum of S1 Quaterphenyl in Solution. Issue 1 (1999) - Toner, W. T.; Matousek, P.; Parker, A. W.; Towrie, M.
Abstract : Intensity changes in Stokes resonance Raman spectra of photoexcited quaterphenyl are found to result from 17 ps timescale changes in resonance frequency and width and also in Franck-Condon displacements. The 766 cm -1 anti-Stokes band shows a significant hot population which decays on a similar timescale. The results show that population relaxation, vibronic coupling and solvent reorganisation are all significant on this timescale.